2012
DOI: 10.1542/peds.2012-0714
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Neonatal Encephalopathy in the Vermont Oxford Network Encephalopathy Registry

Abstract: Clinically recognized asphyxial birth events, indicators of intrauterine exposure to inflammation, fetal growth restriction, and birth defects were each observed in term infants with NE, but much of NE in this large registry remained unexplained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 42 publications
4
48
0
1
Order By: Relevance
“…Given the vulnerability of the fetal/neonatal brain to hypoxia-ischaemia and the known association of neonatal encephalopathy with longer term cerebral palsy and mortality [26][27][28] it is important that at risk fetuses are identified antenatally and strategies put in place to minimize the risk of intrapartum compromise. The strengths of our study are its large size as well as the diverse patient population and the clinically relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the vulnerability of the fetal/neonatal brain to hypoxia-ischaemia and the known association of neonatal encephalopathy with longer term cerebral palsy and mortality [26][27][28] it is important that at risk fetuses are identified antenatally and strategies put in place to minimize the risk of intrapartum compromise. The strengths of our study are its large size as well as the diverse patient population and the clinically relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, previous studies in high-income settings have shown high prevalence of inflammatory indicator (24%) amongst infants with neonatal encephalopathy. 40 A recent US study, examining the association between maternal and neonatal infections and adverse outcomes after neonatal encephalopathy, reported an increase in adverse neurodevelopmental outcomes, but not death, amongst encephalopathic infants with sepsis; however, chorioamnionitis was associated with a lower risk of brain injury and adverse cognitive outcomes were less severe in infants exposed to chorioamnionitis. 41 Although it seems likely that the burden of infectious comorbidity is highest in low-income settings, a high incidence of sepsis has been seen in many of the hypothermia trials preformed in high-income settings (5-14%).…”
Section: Observations On Cytokines/chemokinesmentioning
confidence: 99%
“…30,31 Other studies, using a stricter definition of encephalopathy that automatically excludes most conditions with an antenatal or genetic origin, have found that intrapartum events are the main or a contributing factor in the causal pathway of HIE. 12,[32][33][34] None of the previous studies has used neonatal neuroimaging investigations to confirm the presence of acute hypoxicischemic injury of recent onset and to exclude other causes of encephalopathy.…”
Section: Figurementioning
confidence: 99%